The Work Participation of the Elderly during the COVID-19 Pandemic in Palu City - Kalvin Albert Parinding; Chairil Anwar; Suparman Suparman; Laendatu Paembonan (Budapest International Research and Critics University, 2021)
This study examines the work participation of the elderly population (≥ 60 years) during the COVID-19 pandemic in Palu City. The sample was 80 respondents. The data analysis used probit regression. The results showed that only 36.26 percent of all respondents are still working. The COVID-19 pandemic changes variables affecting work participation of the elderly. The results of the analysis show that only two variables have a significant influence, namely age and health status of the elderly. As the elderly get older, the probability of the elderly participating in the labor market decreases. The elderly with a health condition have a greater probability of entering the labor market than the elderly with poor health conditions. Meanwhile, four variables did not have a significant influence during the COVID-19 pandemic, such as education, gender, status in the household and other sources of income (pension funds and remittance). Work participation is greatly affected by the presence of the COVID-19 pandemic.